Psychometric properties of the Child Oral‐care Performance Assessment Scale. Issue 5 (30th May 2019) - Nair, Rahul; Do, Loc Giang; Luzzi, Liana; Brennan, David Simon; Roberts‐Thomson, Kaye Frances; Spencer, Andrew John
Abstract: Objectives: This study aimed to assess the psychometric properties of Child Oral‐care Performance Assessment Scale (COPAS). Methods: Items for the instrument were developed and pilot tested. This questionnaire was implemented in the Australian National Child Oral Health Study 2012‐2014, whose aims included the assessment of oral care performance. This nationally representative sample of 23 538 respondents with complete data was divided into five groups: a main validation group and four cross‐validation groups, using blocked randomization. Two scales were constructed, full scale with 37 items (COPAS) and a partial scale with a subset of 31 items (COPAS‐Partial). Internal consistency was assessed using Cronbach's alpha. Construct validity was assessed using correlation coefficients, and structural validity was ascertained in the main validation group and confirmed in the cross‐validation groups using structural equation models. Results: Cronbach's alpha for COPAS was 0.95, and for COPAS‐Partial was 0.94. The convergent validity of global satisfaction with oral care and the subscales was r = 0.29‐0.51, and that with the overall scales was r = 0.59 for COPAS and r = 0.59 for COPAS‐Partial. COPAS (Root mean squared error of approximation (RMSEA) = 0.06, Comparative fit index (CFI) = 0.90, Tucker‐Lewis index (TLI) = 0.89, and Coefficient of determination(COD) = 0.99) and COPAS‐Partial (RMSEA = 0.07, CFI = 0.91, TLI = 0.90, COD = 0.97) had adequate fit. Structural invariance was present ( P ‐value = 0.97). Conclusion: There was acceptable structural validity, construct validity and internal consistency in the models tested for COPAS and COPAS‐Partial. COPAS has potential use in the evaluation of the delivery of dental services to children.